(3GdChGFds - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY QJHI GdGOH hPhHI bGd GHQGgje Ydjg GdSdGe ajeG Mci Gddg JYGdi GLYd di dSGf UOb ai GdBNQjf s
(3BNQgG (B:s
(3hai gPG GdNHQ Odjd Ydi Cf GdCeQ GdPj YbOg fhad Hf YHO efGa gPG BNQ ef NQL dfG ef GdChGFd s
(3GdfSNI HgG MhGTs
(3LYdg Ydi YTQI CHhGHs
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3eJaQbGJs